1997
DOI: 10.1515/bchm.1997.378.2.71
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Progelatinase A and Progelatinase A/TIMP-2 Complex by Membrane Type 2-Matrix Metalloproteinase

Abstract: C-terminal truncated membrane-type 2 matrix metalloproteinase (MT2-MMP1-269), comprising prodomain and catalytic domain, was expressed as a soluble protein in Escherichia coli. Unlike the corresponding form of MT1-MMP, which can be isolated as a 31 kDa protein, MT2-MMP1-269 proved to be comparatively instable, and already the freshly isolated preparation displayed several proteins in SDS-PAGE representing MT2-MMP1-269 (33 kDa) and four N-truncated forms with N-termini methionine32 (30 kDa), isoleucine37 (30 kD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 26 publications
0
31
0
1
Order By: Relevance
“…Because purified MT-MMPs cannot readily be evaluated in their membranebound state, most experiments designed to study the function of MT-MMPs have employed secreted (soluble) mutant MT1-MMP recombinants lacking the transmembrane domain (15)(16)(17)(18). Based on these studies, it has been concluded that cleavage of the N-terminal domain of membrane-bound MT-MMPs by furin, presumably in the trans-Golgi network, is required for function of the enzyme in activating progelatinase A and degrading other substrates (15,16,18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Because purified MT-MMPs cannot readily be evaluated in their membranebound state, most experiments designed to study the function of MT-MMPs have employed secreted (soluble) mutant MT1-MMP recombinants lacking the transmembrane domain (15)(16)(17)(18). Based on these studies, it has been concluded that cleavage of the N-terminal domain of membrane-bound MT-MMPs by furin, presumably in the trans-Golgi network, is required for function of the enzyme in activating progelatinase A and degrading other substrates (15,16,18,19).…”
Section: Discussionmentioning
confidence: 99%
“…11 MT1-MMP seems to be the major activator of proMMP-2, mainly via presentation of proMMP-2 by a MT1-MMP-TIMP-2 "receptor". [15][16][17][18] However, the catalytic domains or the fulllength molecules of the other MT-MMPs [19][20][21][22][23] have also been shown in vitro or expressed in mammalian cells, respectively, to activate proMMP-2. Apparently, MT2-MMP is able to perform this activation in a TIMP-2-independent manner.…”
Section: Introductionmentioning
confidence: 99%
“…MT1-MMP appears to be the major activator of MMP-2 as shown using MT1-MMP null mice, however, some activation of MMP-2 in these mice was observed (30). Indeed other members of the MT-MMP sub-family have been shown to activate MMP-2, using either catalytic domains in vitro (MT-MMPs 2, 4, and 5) (13,(31)(32)(33) or the full-length molecule expressed in mammalian cells (MT-MMPs 3, 5, and 6) (6,34,35). However, the requirement for TIMP-2 in MMP-2 activation by MT-MMPs 2-6 has not been demonstrated, nor has the potential role of TIMP-4 in MMP-2 activation by these MT-MMPs been addressed.…”
mentioning
confidence: 95%
“…Expression of MT2-MMP in glioblastomas correlated with MMP-2 activation and degree of malignancy (40), and expression of MT2-MMP in COS cells was found to confer invasiveness (41). Although the soluble MT2-MMP catalytic domain produced in Escherichia coli was shown to activate MMP-2 in the absence of TIMP-2 in vitro (31,32), this was thought to occur due to an unphysiologically high concentration of the MT2-MMP. Other reports are unclear regarding the potential for the cellular activation of MMP-2 by full-length MT2-MMP, and the requirement for TIMP-2 has not specifically been addressed.…”
mentioning
confidence: 99%